Pengaruh Pengalaman Kerja Dan Disiplin Kerja Terhadap Kinerja Karyawan Di Prama Sanur Beach Bali - Wirawan, I Made Adhi; Yogantara, Komang Krishna; Poetranto, Wahjoedi Dwi (Universitas Triatma Mulya, 2023)
The research entitled: The Effect of Work Experience and Work Discipline on Employee Performance at Prama Sanur Beach Bali aims to determine the effect of work experience, and the effect of work discipline on employee performance at Prama Sanur Beach Bali, either partially or simultaneously. The number of respondents taken is as much as 25% of the number of employees at Prama Sanur Beach Bali as many as 86 employees respondents from 345 employees. Meanwhile, data processing using SPSS with multiple regression analysis techniques where the results show that Work Experience and Work Discipline have a significant positive effect either partially or simultaneously. The result is based on the results of the T-test, it is obtained that the calculated T value is 4.696. This T arithmetic value is greater than the T table value of 1.6627 so it can be concluded that there is a partially significant effect between Work Experience on Employee Performance. After being tested partially by using the T-test, the calculated T value was 5.948, the T calculated value was greater than the T table value of 1.6627 so it could be concluded that there was a partial significant effect between Work Discipline on Employee Performance while the calculated F value of 34.473 the value This calculated F is greater than the F table value of 3.10. So it can be concluded that there is a significant influence, namely Work Experience and Work Discipline on Employee Performance simultaneously.